An evaluation of students industrial training courses implementation at higher education - Ambiyar Ambiyar; Asmar Yulastri; Yuzia Eka Putri; Rizky Ema Wulansari (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This article aims to reveal the factual basis regarding the implementation of Students Industrial Training (SIT) course by the bachelor's degree students of Hospitality Management Department from the Faculty of Tourism and Hospitality at the University. The methodology used in this study is mixed method with CSE-UCLA evaluation model. The informants in this study were 35 hospitality management students who were graduated in 2015, the SIT Coordinators, Heads of Tourism Departments, and Supervisors, Managers, Industrial Supervisors, senior staffs, and assistance from the Hotel Food and Beverage department. Data of this research were gathered through observation, questionnaires, and interviews. Those data were analyzed by using descriptive statistics technique. The results showed the average score of the need assessment evaluation component was 4.2 (good), program planning was 4.14 (good), formative evaluation was 4.04 (good), and summative evaluation was 3.98 (enough). This Students Industrial Training Program can be continued by improving the students' knowledge, working skills, and English skills, as well as improving the role of supervisors and instructors/ industrial supervisors in monitoring and providing solutions for the students to overcome problems they faced. Furthermore, this training program needed to improve the quality and quantity of relevant campus facilities and infrastructure to the hospitality industry, and increasing the positive attitude of the students in carrying out the industrial training course.